The Gonad Maturity of Female Osteochillus vittatus in the presence of Ascorbic Acid - Setyaningrum, Nuning; Sugiharto, Sugiharto; Hidayah, Hexa Apriliana (Biosaintifika: Journal of Biology & Biology Education, 2017)
The fishs reproduction status is affected by both fed compositions and vitamins intake lead to determine improvement of eggs quality as well as fish production. The presence of Ascorbic Acid (AA) in the cultivation ponds, might accelerate females gonad maturation and so rematuration. The research aimed to determine: (1) Level gonad maturity of supplementation Ascorbic Acid; (2) Oocyts diameter; (3) Larvae survival rate. The research used experimental methods.The method was a completely randomized design (CRD) of 4 treatments and 4 replications. Treatments were supplementation of AA at different dosages of 0, 600, 1200 and 1800 mg/kg fish-fed ration.The gonad maturity level was analysed descriptively and oocyte diameter and larvae survival rate data were analysed by ANOVA. The result showed that supplementation of AA at a dosage of 1200 mg / kg fish-fed ration accelerated the process of gonad maturity, development of oocyt diameter and larvae survival rate as well as the viability of O. vittatus larvae at 90 rearing days. In this case, level IV gonad maturity was reached at 90 days which characterized by completed vitelogenesis process and oocyte diameter of 1.1 mm. Thus, this study is useful for aquaculture science by providing information on utilization of AA as food supplement in fish culture and also for fish farmer who wish to accelerate O. vittatus reproduction.